Kandungan Logam Berat Merkuri, Timbal dan Cadmium pada Air, Ikan, dan Sedimen di Danau Limboto - Hadiyanto Hadiyanto; Hasim Hasim; Juliana Juliana (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Lake Limboto is the largest lake in Gorontalo province including 15 Lake baggage that will be restored by the government. Pollution occurring in Lake waters is an important issue that needs to get the attention of various parties. Research aims to determine the status of environmental quality of the area, reviewing heavy metals (Hg, Pb, Cd) in water fishes and sediments, knowing the correlation between the fish and sediment. Sampling method is performed on 12 sampling points specified in purpose sampling. The method of analysis is used with government regulation No. 82 year 2001 on water quality and pollution control, measurement of heavy metal concentration SNI 06-6992.2.2004 by using Atomic Absorption Spekphotometer (AAS). The mercury content (Hg) of water in the 0.0019-0.1216 ppm range has exceeded the limits based on quality standards, lead (Pb) ranges between 0.008-0.0463 ppm while cadmium levels (Cd) range 0.007-0.0085 mg/L in general the value difference between stations is not Much. The content of mercury heavy metals in fish 0.0079-0.0631 as well as the heavy metal content of Pb is 0054 mg/L while the cadmium (Cd) content 0.017-0.058 mg/L. The concentration of heavy metals Hg 5.81-5.72 mg/L, the average Pb heavy metal 0.5571 mg/L whereas the heavy metal cadmium 0.6190 mg/L. The correlation of heavy metal mercury with water is an index of 1.00 showing strong relationships while the correlation of the heavy metals Pb 0233 has a weak and negative relationship and the Cd heavy metal is the 0.019 that shows a low correlate.